1985
DOI: 10.1007/bf00318976
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopy of the initial stages of placentation in the pig

Abstract: To elucidate the morphology of the initial stages of epitheliochorial placentation in the pig, material from 10 sows of the Danish Landrace and from one Göttinger minipig gilt from day 13 to day 26 of gestation was processed for scanning and transmission electron microscopy. The observed foetomaternal interaction from day 19 1/2 minipig placenta corresponded well to the observations on the Danish Landrace placenta. From the results and the discussion it was concluded that the following structures were implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
129
0
6

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(144 citation statements)
references
References 41 publications
9
129
0
6
Order By: Relevance
“…This material was described as glycoproteins of great diversity in the differing species and different stages of gestation (Jones et al 1995, Jones et al 1997. In sow placenta, this material is attributed with having functions of adhesion, control and inhibition of the invasive process of the trophoblast, as well as being related to the presence of signaling molecules of hormones, enzymes and growth factors (Dantzer 1985, Dantzer & Leiser 1993.…”
Section: Discus Discus Discus Discus Discussion Sion Sion Sion Sionmentioning
confidence: 99%
“…This material was described as glycoproteins of great diversity in the differing species and different stages of gestation (Jones et al 1995, Jones et al 1997. In sow placenta, this material is attributed with having functions of adhesion, control and inhibition of the invasive process of the trophoblast, as well as being related to the presence of signaling molecules of hormones, enzymes and growth factors (Dantzer 1985, Dantzer & Leiser 1993.…”
Section: Discus Discus Discus Discus Discussion Sion Sion Sion Sionmentioning
confidence: 99%
“…Microvilli of follicle cells projecting toward the oocyte have also been described in amphibians and mammals (Dantzer, 1985;Villecco et al, 2002;Makabe et al, 2006), suggesting that follicle cell microvilli might establish connections with oocytes in many animal species. Considering that, over the past decades, microvilli have been identified in a plethora of epithelia and organisms, we speculate that microvilli might connect apposed epithelia during different developmental stages in several organisms.…”
Section: Apical Protrusions Connect Columnar Cells With Squamous Cellsmentioning
confidence: 97%
“…In camels, Skidmore et al [31] showed that microvilli are completely lost on uterine epithelial cells at attachment only to be later reformed in a much longer profile as the interface of the mature epitheliochorial placenta and this very complete apical membrane flattening in camels has been elaborated on more recently [32]. In pigs, which also have an epitheliochorial placenta, Dantzer [20] commented on progressive loss of uterine epithelial microvilli and flattening of the apical plasma membrane into regions where uterine and trophoblast membranes ran parallel after which microvilli reformed to establish the mature epitheliochorial placenta and in one other epitheliochorial placenta, that of the marsupial mouse, Roberts and Breed [33] have also found flattening and loss of apical microvilli of uterine epithelial cells at attachment in a reaction they described as very similar to that of rats and mice. In the rhesus monkey, Enders et al [34] showed loss of microvilli and other flattened membrane areas on uterine epithelial cell surfaces at attachment and in humans several workers have pointed out similarities between the behaviour of rodent and human uterine epithelial cell apical plasmalemmas during early pregnancy [35][36][37][38][39] as we shall examine in more detail later.…”
Section: The Apical Plasma Membrane In Other Animalsmentioning
confidence: 99%